Integrating Micro and Smart Grid-Based Renewable Energy Sources with the National Grid in Bangladesh - A Case Study - Zaman, Md Rakibur; Halim, Md Abdul; Khan, Md. Yakub Ali; Ibrahim, Salah; Haque, Abrarul (Control Systems and Optimization Letters, 2024)
The worldwide quest for sustainable energy solutions has led to a thorough investigation of the integration of renewable energy sources based on micro and smart grids into national electricity systems. This case study focuses on Bangladesh's particular situation, as a nation attempting to find workable solutions to its energy problems. The study explores how cutting-edge smart grid technology and decentralized energy systems, such as microgrids, can be integrated to improve the country's energy environment. The report commences by evaluating the current condition of Bangladesh's national grid, outlining the obstacles that still need to be overcome, and stressing the importance of having a variety of reliable energy sources. After that, the emphasis switches to microgrids, where their potential to support energy autonomy, harvest renewable energy locally, and lessen load on the centralized grid is examined.  A thorough analysis of the technical, financial, and legal factors is carried out, considering how well micro and smart grid technologies work with the country's grid infrastructure. A case study that highlights a particular implementation in a chosen area of Bangladesh provides useful information. To assess the effectiveness and difficulties of the integration process, key metrics such the penetration of renewable energy, grid stability, and economic viability are described. In addition to providing resilience against power outages, increasing energy efficiency, and promoting a sustainable energy ecosystem, the results highlight the potential advantages of a synergistic strategy in which micro and smart networks supplement the national grid. Regulatory framework, technology standardization, and community participation challenges are all noted, and these call for the implementation of policy interventions and strategic planning. This case study provides insightful information about how Bangladesh's national system integrates renewable energy sources based on micro and smart grids. In the context of a developing nation's energy transition, it advocates for a comprehensive approach that considers technological breakthroughs, economic viability, and regulatory frameworks to unlock the full potential of decentralized and smart grid solutions.